Inefficient processing time as hidden time loss in assembly operations - Ebrahim, Zuhriah; Muhamad, Mohd Razali; Abdul Rasib, Amir Hamzah (Penerbit Universiti, UTeM, 2018)
Hidden Time Loss (HTL) occurs along the production processes that have a significant effect to productivity. Overall Equipment Efficiency (OEE) is the most popular performance measurement tool used in the production line. However,OEE doesn’t really fit in measuring operation performance of manual assembly process and semi-auto assembly process.In this case,there would be the amount of HTL have occurred along the assembly processes that become critical when to involve high product variety in the same production line.Thus,the purpose of this paper is to introduce Inefficient Processing Time (IPT) as one of the component of Time Loss Measures (TLM) in the manual assembly process and semi-auto assembly process. The structure of IPT is developed through a thorough literature study on manufacturing operations and its performance measures.The IPT structure is validated by using case study at five automotive manufacturing companies.The results show that the IPT can contribute to HTL in the manual assembly process and semi-auto assembly process.